2008
DOI: 10.1002/hep.21951
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of suppressor of cytokine signaling 3 by an oncolytic adenovirus induces potential antitumor activities in hepatocellular carcinoma

Abstract: S ignal transducer and activator of transcription (STAT) proteins comprise a family of transcription factors latent in the cytoplasm that participate in normal cellular events. STATs are activated in response to cytokines and growth factors and are recruited to specific receptor phosphotyrosines at which they are phosphorylated by Janus kinases (JAKs). After activation, STATs dimerize and translocate to the nucleus, at which they can activate target gene transcription related to cell proliferation and survival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 36 publications
0
34
0
Order By: Relevance
“…It has been shown that deleting a small viral protein E4-orf3 can bring higher safety to the oncolytic adenovirus; 22 and liver cancer suppressor gene, such as HCCS1 or SOCS3, Liver cancer-targeting gene-viro-therapy X Liu et al have been shown to specifically inhibit liver tumorigenesis. 19,23 It will be our future interest to improve the presently used HCC-targeting OV Ad Á AFP Á D55 and select more appropriate antitumor genes using these strategies. Figure 6 Histopathologic, immunohistochemical and terminal deoxynucleotidyl transferase-mediated dUTP-biotin nick end labeling (TUNEL) analyses of tumor sections.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that deleting a small viral protein E4-orf3 can bring higher safety to the oncolytic adenovirus; 22 and liver cancer suppressor gene, such as HCCS1 or SOCS3, Liver cancer-targeting gene-viro-therapy X Liu et al have been shown to specifically inhibit liver tumorigenesis. 19,23 It will be our future interest to improve the presently used HCC-targeting OV Ad Á AFP Á D55 and select more appropriate antitumor genes using these strategies. Figure 6 Histopathologic, immunohistochemical and terminal deoxynucleotidyl transferase-mediated dUTP-biotin nick end labeling (TUNEL) analyses of tumor sections.…”
Section: Discussionmentioning
confidence: 99%
“…33 Other evidence suggesting a role of STAT3 in tumorigenesis included findings that deletion of hepatic SOCS3, an inhibitor of STAT3, elevated STAT3 activation in the liver and accelerated DEN-induced liver tumorigenesis, 34 whereas overexpression of SOCS3 inhibited HCC cell growth. 35 Moreover, several cytokines (IL-6, IL-6 family cytokines, IL-22, leptin, etc) that activate STAT3 in hepatocytes have also been shown to promote HCC cell growth in vitro and in vivo. [17][18][19]36 Finally, as we show in this study, deletion of STAT3 in hepatocytes prevents DEN-induced HCC development, which was also reported previously.…”
Section: Stat3 Is a Pro-oncogenic Factor That Promotes Liver Tumorigementioning
confidence: 99%
“…Our previous studies demonstrated that oncolytic adenoviral vectors carrying apoptosis-inducing genes induce strong antitumor activity (10)(11)(12). As we deleted the CR2 region of the vector genome which promotes the native E1A by hTERT, the oncolytic adenoviral vector was selectively amplified in most tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…As we deleted the CR2 region of the vector genome which promotes the native E1A by hTERT, the oncolytic adenoviral vector was selectively amplified in most tumor cells. Meanwhile, endogenous major late promoter (MLP) in the adenoviral genome was found to promote cpp-SCOS3 expression, and the promoter contributed to the tumor-specific viral replication of adenoviral vectors and more effectively attenuated tumor cell malignancy (10).…”
Section: Introductionmentioning
confidence: 99%